Epilepsy With Internal and External Risk Factors in a Middle-Aged Woman : A Family-Oriented Case Report - Zakiah; Hidayati, Nurul (Family Medicine Department, Faculty of Medicine, Brawijaya University, 2026)
Epilepsy is a chronic neurological disorder characterized by recurrent unprovoked seizures. In low- and middle-income countries, delays in diagnosis and mismanagement at primary care level remain common. This study describe a case of epilepsy in a middle-aged woman with internal and external risk factors, managed through family-centered and community-oriented approaches. A descriptive case report of a 42-year-old woman who presented to Kendalsari Primary Health Center with recurrent generalized tonic-clonic seizures for one year. Data were collected from anamnesis, physical examination, family assessment, and home visits, then analyzed using the Mandala of Health framework. The patient experienced five to six seizure episodes in the past year, often triggered by fatigue. She initially sought treatment from a midwife who prescribed betahistine and dexamethasone, before being referred to a neurologist and receiving appropriate antiepileptic therapy. Family APGAR score was 8, indicating good family function, though financial constraints and limited knowledge delayed proper medical care. Home visits revealed normal functional status but persistent unhealthy lifestyle factors, such as prolonged mobile phone use and frequent consumption of fatty foods. Comprehensive management of epilepsy requires not only biomedical treatment but also family support, lifestyle modification, and appropriate primary care referral. Family conference and community involvement play an essential role in long-term disease control.